Learning management system technologies and software solutions for online teaching : tools and applications - Kats, Yefim (Hershey, PA : Information Science Reference, 2010)
'This book gives a general coverage of learning management systems followed by a comparative analysis of the particular LMS products, review of technologies supporting different aspect of educational process, and, the best practices and methodologies for LMS-supported course delivery'--Provided by publisher.
Includes bibliographical references (p. 410-444) and index.
Keywords: Internet in higher education; Education, Higher -- Computer-assisted instruction; Organizational effectiveness; System analysis